Los servicios médicos y la satisfacción del paciente en el hospital San Patricio en la ciudad de Guaranda, provincia Bolívar, año 2024 - Carrera Garofalo, Leidy Marilin (2024)
Patient satisfaction is one of the fundamental strategic objectives for any organization, in this case, it is of great importance for the health facility Hospital "San Patricio" and the health services it offers to the population of Guaranda. The objective of this research is to determine the relationship between the medical services offered by the facility and the perception of satisfaction of the patient who comes to the health center's facilities. Through a descriptive, inductive and deductive study, data collection tools such as surveys were used to collect and interpret the data obtained from the 63 participants. For the internal consistency, Crobanch's alpha was 0.72, which confirms the reliability and validity of the questionnaire applied in the research. With the information obtained, we proceeded to establish an improvement plan focused on patient satisfaction at the "San Patricio" Hospital and to mitigate the risks caused by the critical nodes identified during the research.